Time–frequency beamforming for nondestructive evaluations of plate using ultrasonic Lamb wave. (March 2015) - Han, Je-Heon; Kim, Yong-Joe
Abstract: The objective of this study is to detect structural defect locations in a plate by exciting the plate with a specific ultrasonic Lamb wave and recording reflective wave signals using a piezoelectric transducer array. For the purpose of eliminating the effects of the direct excitation signals as well as the boundary-reflected wave signals, it is proposed to improve a conventional MUSIC beamforming procedure by processing the measured signals in the time–frequency domain. In addition, a normalized, damped, cylindrical 2-D steering vector is proposed to increase the spatial resolution of time–frequency MUSIC power results. A cross-shaped array is selected to further improve the spatial resolution and to avoid mirrored virtual image effects. Here, it is experimentally demonstrated that the proposed time–frequency MUSIC beamforming procedure can be used to identify structural defect locations on an aluminum plate by distinguishing the defect-induced waves from the excitation-generated and boundary-reflected waves. Highlights: Time–frequency beamforming algorithms are proposed for structural damage detection. They are to suppress the effects of excitation- and boundary-induced waves. Experimental data are obtained with an aluminum panel. The experiment data are used to validate the proposed beamforming approaches.